REPRESENTING VICTIM OF VIOLENCE IN NEWS: FEMALE VICTIM OF UGM’S CASE IN THE JAKARTA POST’S ARTICLES - Sabta Diana; Albert Tallapessy; Abdul Haris Nusa Bela (Universitas Sebelas Maret, 2019)
This study investigates the existence of Gender-Based Violence (GBV) in one of Indonesia English language newspaper The Jakarta Post. This research aims to reveal the existence of this GBV practice in five selected articles under the case of sexual assault happened to Agni, one of UGM students. This research uses qualitative research where there are 131 clauses selected to be analyzed. The analysis uses the Critical Discourse Analysis Fairclough’s model (1989) as a framework, involving Halliday’s Systemic Functional Linguistics (SFL) (2004), Wood’s gendered media (1994), and mass media discourse. The result shows that gender-based violence practice does exist on those selected articles through the use of linguistic tools applied by the journalists. This indication related to three things. They are a misrepresentation of women, rape narrative, and objectivity, where women are depicted to be submissive and passive in media. The result also finds that patriarchal culture also influences the way of The Jakarta Post in presenting the issue about violence which represents that the media abuses the victim of the issue and provides the existence of gender-based violence that The Jakarta Post presents in their articles. Keywords: Critical Discourse Analysis, Systemic Functional Linguistics, media discourse, The Jakarta Post, gender-based violence,